An ultimatum game with multidimensional response strategies - Werner Güth; M. Vittoria Levati; Chiara Nardi; Ivan Soraperra (Friedrich Schiller University Jena and Max Planck Institute of Economics, 2014)
We enrich the choice task of responders in ultimatum games by allowing them to independently decide whether to collect what is offered to them and whether to destroy what the proposer demanded. Such a multidimensional response format intends to cast further light on the motives guiding responder behavior. Using a conservative and strin- gent approach to type classification, we find that the overwhelming majority of responder participants choose consistently with outcome-based preference models. There are, however, few responders that destroy the proposers demand of a large pie share and concurrently reject their own offer, thereby suggesting a strong concern for integrity.
Keywords: C72; C91; D63; D74; 330; experiments; incomplete information; social preferences; ultimatum